(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article presents the results of research on the topic of development of modern communicative culture by means of Internet resources. The relevance of the issue of communication due to the information revolution and the transition to online life during the epidemic is defined. It has been proved that Internet resources became a connection between people. The changes in the features of communication in recent years are defined. The peculiarities of communication on the Internet network are indicated. The results of a psychological survey on the popularity of online communication, conducted online with the help of Google Forms. The survey shows the interest of people in online communication.